Methodology of Using the Logistics of Pedagogical Innovations in the Educational Cluster Environment - Nargiza Talipjanovna Madgapilova (Euro Asian Journal Publishing, 2024)
In the article discuses about the logistics of pedagogical innovations in the environment of the educational cluster
Keywords: Educational cluster; practice-oriented direction of professional education; social sphere of society